Anoplotettix sathyiancii Dlabola, 1970 (Homoptera, Auchenorrhyncha, Cicadellidae, Deltocephalinae) Üzerine Taksonomik Bir Araştırma - Kartal, Veysel; Zeybekoğlu, Ünal (My University, 1997)
In this study the specimens belonging to Anoplotettix sahtyiancii Dlabola, 1970 species which identified from Sakarya were examined and its taxonomical characteristics were compared with original diagnosis and unidentifed characters which is not given previously were determined with the help of figures.
A taxonomical study on anoplotettix sahtyiancii diabola, 1970 (Homoptera, Auchenorrhyncha, Cicadellidae, Deltocephalinae)
Keywords: Biyoloji